Description of the Postlarval Stages of Dactylochelifer gracilis Beier, Pseudoscorpiones: Cheliferidae - Nassirkhani, Mahrad; Harvey, Mark S. (International Journal of Zoology, 2013)
A study of the free-living developmental stages of Dactylochelifer gracilis Beier, 1951, is presented based on 68 specimens of all nymphal and adult stages, collected from two locations in Iran. Basic differences of all stages are characterized by size, pedipalpal ratios, and the addition of trichobothria and setae during development.